Regulators mount up: the metabolic roles of apoptotic proteins - Schofield, James H.; Schafer, Zachary T. (Frontiers in Cell Death, 2023)
The induction of apoptosis, a programmed cell death pathway governed by activation of caspases, can result in fundamental changes in metabolism that either facilitate or restrict the execution of cell death. In addition, metabolic adaptations can significantly impact whether cells in fact initiate the apoptotic cascade. In this mini-review, we will highlight and discuss the interconnectedness of apoptotic regulation and metabolic alterations, two biological outcomes whose regulators are intertwined.